Etiology, Treatments, and Outcomes of Patients With Severe Community-Acquired Pneumonia in a Large U.S. Sample*. Issue 7 (22nd February 2022) - Haessler, Sarah; Guo, Ning; Deshpande, Abhishek; Zilberberg, Marya D.; Lagu, Tara; Lindenauer, Peter K.; Imrey, Peter B.; Rothberg, Michael B.
Abstract : OBJECTIVES: Compare the clinical practice and outcomes in severe community-acquired pneumonia (sCAP) patients to those in non-sCAP patients using guideline-defined criteria for sCAP. DESIGN: Retrospective observational cohort study. SETTING: One hundred seventy-seven U.S. hospitals within the Premier Healthcare Database. PATIENTS: Hospitalized adult (≥ 18 yr old) patients with pneumonia. MEASUREMENTS AND MAIN RESULTS: Adult patients (≥ 18 yr old) with a principal diagnosis of pneumonia or a secondary diagnosis of pneumonia paired with a principal diagnosis of sepsis or respiratory failure were included. Patients with at least one guideline-defined major criterion for severe pneumonia were compared with patients with nonsevere disease. Among 154, 799 patients with pneumonia, 21, 805 (14.1%) met criteria for sCAP. They had higher organ failure scores (1.9 vs 0.63; p < 0.001) and inpatient mortality (22.0 vs 5.0%; p < 0.001), longer lengths of stay (8 vs 5 d; p < 0.001), and higher costs (20, 046 vs 7, 543; p < 0.001) than those with nonsevere disease. Patients with sCAP had twice the rate of positive blood cultures (10.0% vs 4.5%; p < 0.001) and respiratory cultures (34.2 vs 21.1%; p < 0.001) and more often had isolates resistant to first-line community-acquired pneumonia antibiotics (10% of severe vs 3.1% of nonsevere; p < 0.001). Regardless of disease severity, Streptococcus pneumoniae was the most common pathogen recovered from blood cultures and Staphylococcus aureus and Pseudomonas species were the most common pathogens recovered from the respiratory tract. Although few patients with sCAP had cultures positive for a resistant organism, 65% received vancomycin and 42.8% received piperacillin-tazobactam. CONCLUSIONS: sCAP patients had worse outcomes and twice the rate of culture positivity. S. aureus and S. pneumoniae were the most common organisms in respiratory and blood specimens, respectively. Although only recommended for sCAP patients, nearly all pneumonia patients received blood cultures, a quarter of nonsevere patients received sputum cultures, and treatment with broad-spectrum agents was widespread, indicating fertile ground for antimicrobial and diagnostic stewardship programs.